On the Effectiveness of the Spatial Constructions with Stergen and Their Use (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2023)
Today, in domestic and foreign construction practice, spatial constructions with earthquake-resistant beams are widely used. The article analyzes the work carried out on the study of the effectiveness of their use and summarizes the relevant conclusions.